Hubungan Anemia dengan Kualitas Hidup Pasien PGK yang Menjalani Hemodialisis - Zuliani, Peri; Amita, Dita (Program Studi Ilmu Keperawatan, Fakultas Ilmu Kesehatan Universitas Muhammadiyah Bengkulu, 2020)
Chronic Kidney Disease (CKD) is a progressive and irreversible disorder of renal function, in which the body's ability to fail to maintain metabolism and balance of fluids and electrolytes, causing uremia. The purpose of this study in general was to determine the relationship between hemoglobin levels and quality of life in chronic kidney disease patients undergoing hemodialysis at dr. M. Yunus Bengkulu. This type of research is descriptive analytic with cross sectional approach. The study sample was 64 patients with CKD who underwent hemodialysis at the hemodialysis installation with accidental sampling technique. The results showed that most patients with chronic kidney disease who underwent haemodialysis (71.9%) had severe anemia and most (56.3%) had a poor quality of life. Chi square test results obtained Ï value 0,000 (Î± = 0.05). Conclusion, There is a statistically significant correlation between anemia and quality of life in CKD patients undergoing hemodialysis in the RDUD Dr. Hemodialysis room. M. Yunus. Suggested to Dr. Hospital M. Yunus Bengkulu to control the incidence and symptoms of anemia experienced by CKD patients.Â Keywords: Anemia, Hemodialysis, quality of life, CKD